COMPLEMENTARY INTERVENTION IN POSTPARTUM WOMEN WITH COMBINATION THERAPY OF BETEL LEAF DECOCTION AND BINAHONG TO ACCELERATE HEALING PERINEUM PAIN - Silvia Mona (Yayasan Media Utama Sains, 2024)
One of the main causes of maternal mortality in developing countries such as Indonesia is puerperal infection. One of them is perineal wounds caused by childbirth, which, if not treated, has the potential to cause infection due to the entry of germs through the wound sutures. This research design is a Quasy experiment, a posttest-only control group design. The population was postpartum mothers, with a sample size of 20 people taken by simple random sampling. The study results were then analyzed univariately and bivariately using the t-test statistical test. Of the ten respondents from the experimental group studied, the average healing time of perineal wounds after the use of a combination of betel leaf decoction water and binahong leaves was 3.00 days, while in the control group, it was 7.80, meaning that the experimental group was four days faster than the control group. The results of statistical tests with independent t-tests with α = 0.05 obtained p value = 0.001, which means p-value <0.05; thus, there is an effect of using betel leaf decoction water and binding leaves on perineal wound healing time.